MENGHITUNG PERKALIAN JARI TANGAN DI MI 02 KEMBANG KERANG - Munir, muhammad munir; hijriati, Hijriati Sholehah; Lisnawati, Lisnawati; Tarmizi, Muh. Tarimizi Tahir (Empowerment: Jurnal Pengabdian pada Masyarakat, 2021)
The ability to count is one of the important abilities in everyday life, it can be said that all activities of human life require this ability. this is a separate problem for teachers considering that learning at the primary and secondary education levels has differences where teachers in primary schools must master various materials from all subjects. The training method used is lecture, discussion, practice, and question and answer methods. Based on data, about 83.3% of teachers are enthusiastic about participating in the training and 16.7% of teachers who are not very enthusiastic about participating in the training. This shows that PKM activities with multiplication training using fingers are responded well and are in demand by teachers. There are several obstacles related to counting using finger media, namely errors in calculating line segments, distinguishing multiplier numbers and multiplied numbers. Therefore, we hope that teachers will often repeat or practice themselves by looking at the guidelines that have been given so that there are no mistakes in teaching students.